Slow Light Rainbow Trapping in a Uniformly Magnetized Gyromagnetic Photonic Crystal Waveguide - Chen, Jianfeng; Qin, Qiumeng; Peng, Chaoqun; Liang, Wenyao; Li, Zhi-Yuan (Frontiers in Materials, 2021)
We present a hybrid gyromagnetic photonic crystal (GPC) waveguide composed of different GPC waveguide segments possessing various cylinder radii and waveguide widths but biased by a uniform external magnetic field. We demonstrate in frequency and time domains that based on the strong coupling of two counter-propagating topologically protected one-way edge states, the intriguing slow light rainbow trapping (SLRT) of electromagnetic (EM) waves can be achieved, that is, EM waves of different frequencies can be slowed down and trapped at different positions without cross talk and overlap. More importantly, due to the existence of one-way edge states, external EM waves can be non-reciprocally coupled to the SLRT waveguide channel, although the incident position of the EM wave is far away from the waveguide channel. Besides, the frequency range of the slow light states can also be easily regulated by tuning the intensity of an external magnetic field, which is very beneficial to solve the contradiction between slow light and broad bandwidth. Our results can be applied to the design of high-performance photonic devices, such as an optical buffer, optical switch, and optical filter.